THE ROLE OF BANKING INQUIRIES IN REDUCING BANKING RISKS - Lecturer. Alyaa Kadhim Ayal; Assistant Prof. Mustafa Salam Abdulrida (Scholars Digest Publishing, 2023)
The management of commercial banks resorts to several different means in order to mitigate the severity of the financial risks to which they are exposed as a result of their dealings with different sectors and many customers. In order to protect itself from these risks, perhaps the best means used by the bank’s management is the banking inquiry method, which is generated by collecting information about the borrowers in order to analyze their financial reality and indicate the extent of their ability to fulfill their obligations towards the bank. The guarantee of the bank to recover its rights from the borrowers constitutes a factor for measuring the success of the administration or not, as the non-return of these funds exposes the bank to large financial losses and prevents it from fulfilling its financial obligations towards others, and the sobriety of the bank’s credit policy can reduce exposure to such risks, And the banking inquiry has a great role in obtaining the necessary information for the purpose of knowing and determining the personality and behavior of the customer through many sources, which are represented by [the customer himself, internal sources from the bank, external sources (outside the bank)].